2020
DOI: 10.1016/j.ijid.2020.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of culture positive Tuberculosis and utility of a clinical diagnostic tool for the diagnosis of Tuberculosis among HIV Infected Children attending HIV/AIDS Care and Treatment in Dodoma Municipality, Central Tanzania

Abstract: To evaluate the performance of the modified Keith Edwards TB clinical diagnostic tool among HIV infected children. Methods: Cross sectional study of 252 HIV infected children < 15 years old suspected with TB at four HIV/AIDS Care Clinics in Dodoma, Tanzania from November 2018 -March 2019. The modified Keith Edwards TB clinical diagnostic tool was compared to gastric aspirates, lymphnode aspirates or sputum gene x-pert MTB/RIF and TB culture. Sensitivity, specificity, negative and positive predictive value of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…7 Some studies have reported good performances with a sensitivity varying between 76.9 and 91% and specificity between 88 and 90%,while others have found poor performances with a sensitivity of 85% and a specificity of 25%. [25][26][27] In addition, the interpretation of the scoring system is biased in early stage of disease regarding duration of cough, nutritional status, lack of improvement in nutritional status, unexplained fever with no response to antimalarial drugs and/or two antibiotics. Considering the items of this score, the score could be higher in those with extrapulmonary TB than pulmonary TB.…”
Section: Discussionmentioning
confidence: 99%
“…7 Some studies have reported good performances with a sensitivity varying between 76.9 and 91% and specificity between 88 and 90%,while others have found poor performances with a sensitivity of 85% and a specificity of 25%. [25][26][27] In addition, the interpretation of the scoring system is biased in early stage of disease regarding duration of cough, nutritional status, lack of improvement in nutritional status, unexplained fever with no response to antimalarial drugs and/or two antibiotics. Considering the items of this score, the score could be higher in those with extrapulmonary TB than pulmonary TB.…”
Section: Discussionmentioning
confidence: 99%